The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/evan.21892
|View full text |Cite
|
Sign up to set email alerts
|

New horizons in reconstructing past human behavior: Introducing the “Tübingen University Validated Entheses‐based Reconstruction of Activity” method

Abstract: An accurate reconstruction of habitual activities in past populations and extinct hominin species is a paramount goal of paleoanthropological research, as it can elucidate the evolution of human behavior and the relationship between culture and biology. Variation in muscle attachment (entheseal) morphology has been considered an indicator of habitual activity, and many attempts have been made to use it for this purpose. However, its interpretation remains equivocal due to methodological shortcomings and a pauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 85 publications
(238 reference statements)
0
51
0
Order By: Relevance
“…For instance, previous applications of the V.E.R.A. protocols to fossil hominin hand skeletons (Karakostis & Harvati, 2021; Karakostis et al, 2018) focused exclusively on entheses that have shown consistent differences across documented humans with distinct lifelong occupational activities (Karakostis et al, 2017). Similar recommendations have been made for any skeletal feature used for reconstructing activity in the past (e.g., see Copes et al, 2018; Lieberman et al, 2004; Peacock et al, 2018; Wallace et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, previous applications of the V.E.R.A. protocols to fossil hominin hand skeletons (Karakostis & Harvati, 2021; Karakostis et al, 2018) focused exclusively on entheses that have shown consistent differences across documented humans with distinct lifelong occupational activities (Karakostis et al, 2017). Similar recommendations have been made for any skeletal feature used for reconstructing activity in the past (e.g., see Copes et al, 2018; Lieberman et al, 2004; Peacock et al, 2018; Wallace et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Following the V.E.R.A. method (Karakostis & Harvati, 2021), four entheseal surfaces were delineated using image filtering techniques based on surface elevation, coloration, and surface complexity (Karakostis & Harvati, 2021; Karakostis et al, 2018, 2019a, b, 2021; Karakostis & Lorenzo, 2016). In this study, we provide a pipeline figure of the V.E.R.A method based on the humerus deltoid tuberosity (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The musculus flexor pollicis brevis and the musculus abductor pollicis brevis insert on the medial tubercle. Therefore, these tubercles comprise muscle attachment sites (entheses), of which relative robusticity is experimentally shown to be affected by habitual manual activity (Karakostis et al 2017; Karakostis & Harvati, 2021). Here we show that the robusticity of these tubercles is directly related to robusticity and proportions of proximal hand phalanges themselves.…”
Section: Discussionmentioning
confidence: 99%